Predictors to Achieve Normal Nutrition Status: Longitudinal Study among HIV Children on Antiretroviral Treatment in Bali - Haryadi; Anak Agung Sagung Sawitri; Ketut Dewi Kumara Wati; I Wayan Gede Artawan Eka Putra; Ketut Tuti Parwati Merati (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Malnutrition is common in children with HIV/AIDS. Antiretroviral therapy (ART) improves the nutritional status; however, information about predictors affecting the changes of nutritional status is limited and inconsistent. Methods: The retrospective survival study analyzed secondary data of 84 undernourished children receiving ART in Sanglah Central Hospital in 2010 to 2015. Demographic, clinical and socio-economic characteristics at ART initiation were linked to the achievement of normal nutritional status (z-score ≥ -2 SD). Kaplan Meier analysis was used to obtain the incidence rate and median time and cox proportional hazards models to identify its predictors. Results: Of the 73.81% of children achieved a normal nutrition status with the incidence of children achieving normal nutritional was 19 per 100 child months, and a median time of 4 months 10 days. Children with birth weight ≥2500 gr (AHR=5.41; 95%CI: 1.76-16.61), without candidiasis (AHR=3.72; 95%CI: 1.27-10.93), Clinical WHO Stage III (AHR=1.6; 95%CI: 1.08-4.24), Clinical WHO Stage II (AHR=4.49; 95%CI: 1.95-10.79) and early ART intiation (AHR=0.91; 95%CI: 0.83-0.98) were predictors to achieve normal nutritional status. Conclusion: Clinical characteristics of children are predictors of achieving a normal nutritional status.